Genome‐wide CNV analysis in 221 unrelated patients and targeted high‐throughput sequencing reveal novel causative candidate genes for colorectal adenomatous polyposis. Issue 6 (30th September 2014) - Horpaopan, Sukanya; Spier, Isabel; Zink, Alexander M.; Altmüller, Janine; Holzapfel, Stefanie; Laner, Andreas; Vogt, Stefanie; Uhlhaas, Siegfried; Heilmann, Stefanie; Stienen, Dietlinde; Pasternack, Sandra M.; Keppler, Kathleen; et al.
<x xml:space="preserve">Abstract</x> To uncover novel causative genes in patients with unexplained adenomatous polyposis, a model disease for colorectal cancer, we performed a genome‐wide analysis of germline copy number variants (CNV) in a large, well characterized APC and MUTYH mutation negative patient cohort followed by a targeted next generation sequencing (NGS) approach. Genomic DNA from 221 unrelated German patients was genotyped on high‐resolution SNP arrays. Putative CNVs were filtered according to stringent criteria, compared with those of 531 population‐based German controls, and validated by qPCR. Candidate genes were prioritized using in silico, expression, and segregation analyses, data mining and enrichment analyses of genes and pathways. In 27% of the 221 unrelated patients, a total of 77 protein coding genes displayed rare, nonrecurrent, germline CNVs. The set included 26 candidates with molecular and cellular functions related to tumorigenesis. Targeted high‐throughput sequencing found truncating point mutations in 12% (10/77) of the prioritized genes. No clear evidence was found for autosomal recessive subtypes. Six patients had potentially causative mutations in more than one of the 26 genes. Combined with data from recent studies of early‐onset colorectal and breast cancer, recurrent potential loss‐of‐function alterations were detected in CNTN6, FOCAD (KIAA1797), HSPH1, KIF26B, MCM3AP, YBEY and in three genes from the ARHGAP family. In the canonical Wnt pathway oncogene CTNNB1 (β‐catenin), two potential gain‐of‐function mutations were found. In conclusion, the present study identified a group of rarely affected genes which are likely to predispose to colorectal adenoma formation and confirmed previously published candidates for tumor predisposition as etiologically relevant.